The Development of An Assessment Instrument for Improving Students’ Analytical Thinking Abilities - Sihotang, Ijah Mulyani; Fatmawarni, Fatmawarni (Lembaga Riset Mutiara Akbar, 2025)
This study addresses the low analytical thinking skills observed among accounting education students, particularly in mastering journal entry concepts. Analytical ability is a crucial component of higher-order thinking skills (HOTS), which are essential for success in accounting practice. To respond to this issue, this research aimed to develop a valid and reliable assessment instrument using the Thiagarajan four-D model (Define, Design, Develop, and Disseminate), although the process was limited to the third stage. The study employed a research and development (R&D) approach, with data collected through tests and expert validation, and analyzed using descriptive qualitative methods. The results showed that the developed instrument met the criteria of clarity, relevance, accuracy, and language quality. It also demonstrated high reliability with a Cronbach’s alpha of 0.712. However, students' performance on the instrument revealed an average score of 37.66 out of 100, indicating low analytical thinking skills. The study concludes that while the instrument is feasible, further pedagogical innovation is needed to enhance student competencies.